Public Mental Health Crisis during COVID-19 Pandemic, China - Dong, Lu; Bouey, Jennifer (Emerging infectious diseases, 2020)
The 2019 novel coronavirus disease emerged in China in late 2019-early 2020 and spread rapidly. China has been implementing emergency psychological crisis interventions to reduce the negative psychosocial impact on public mental health, but challenges exist. Public mental health interventions should be formally integrated into public health preparedness and emergency response plans.